Observation of an anomalous Hall effect in single-crystal Mn3Pt. (1st February 2023) - Zuniga-Cespedes, Belén E; Manna, Kaustuv; Noad, Hilary M L; Yang, Po-Ya; Nicklas, Michael; Felser, Claudia; Mackenzie, Andrew P; Hicks, Clifford W
Abstract: The Mn3 X family of compounds was the first in which a large anomalous Hall effect (AHE) was predicted to arise from a purely antiferromagnetic structure, due to the Berry curvature in momentum space. Nearly simultaneously with this prediction, a large AHE was observed experimentally in one of the hexagonal members of this family, Mn3 Sn. Aligning antiferromagnetic domains, a necessary step for observation of the AHE, is more challenging for the cubic members of the Mn3 X family, due to a combination of smaller spontaneous ferromagnetic moments and much stronger magnetic anisotropy. Here, we use a combination of uniaxial stress and applied magnetic field to align domains of bulk single-crystal Mn3 Pt, and demonstrate for the first time a substantial AHE in a bulk sample of a cubic member of the Mn3 X family. The AHE remains locked in with essentially no quantitative variation when the stress is ramped back to zero, which shows that it is not a consequence of any stress-induced ferromagnetic moment.